THE COLLECTION OF LITHUANIAN HYMNALS OF LITHUANIA MINOR IN KAUNAS COUNTRY PUBLIC LIBRARY - DAMBRAUSKIENĖ, RAMUNĖ (Knygotyra, 2015)
Fourty seven percent of the repertoire of Lithuanian literature published in Lithuania Minor in the period 1808–1941 consists of religious literature. The publishing of this literature was promoted by the Evangelical Lutheran Church and the Pietistic religious movement which originated in the 18th century. The Kaunas Country Public Library preserves a collection of Lithuanian hymnals published in Lithuania Minor in the years 1850–1936. The collection consists of 142 hymnals which make 34.7% of the hymnals published in the years 1808–1936. It contains rare editions: 4 uniques, 11 curios, 15 especially rare hymnals. An important part of the cultural heritage of the books that reflect the manners and religious practices of people in this region is binding of hymnals, super-ex-libris and provenances. Wafers, stamps and vignettes – promotional marks of book binders – allow identifying the authors of hymnals and super-ex-librises; 74 books are signed with various marks. There are 73 personal names among the marks of the hymnal collection. The major part of the provenances consists of marks of property (58), promotional marks of book binders (14), stamps (10), superexlibrises (9), exlibrises (1) and marginalia (17). The property records and marginalia perpetuated names and place-names, dates connected to the book owners and their relatives, fragments of favorite religious texts and records of important life events. It is a sign of the extinct culture of Lithuania Minor, which remained on the pages of the publications. The books of Lithuania Minor are rare because of the historical and political circumstances of the region, a decay of lowquality paper used in the 19th and the first part of the 20th century, and small book editions. Due to the small number of extant copies and the provenances they contain, the collection is an important part of Lithuania Minor printing and cultural heritage, which complements Lithuanian national bibliography.
Keywords: ...